2019
DOI: 10.1055/s-0039-1692413
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Fluid Prescription Practices in Critically Ill Children: A Shift in Focus from Natremia to Chloremia?

Abstract: Our objective is to evaluate intravenous (IV) fluid prescription practice patterns in critically ill children in the first 72 hours of pediatric intensive care unit (PICU) admission and to evaluate the incidence and predictors of hyperchloremic metabolic acidemia (HCMA) and the association between HCMA and adverse outcomes. This retrospective cohort study was conducted in two tertiary-care Canadian PICUs. Children aged 0 to 18 years admitted to the PICU between January 2015 and January 2016 who received at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…The median length of hospital stay of all the included patients was 17 days (IQR 9-34). The group receiving hypotonic solutions had a longer stay (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) than the group receiving isotonic solutions (14 days IQR 8-30) (p = 0.000). The use of hypotonic solutions was associated with 8 more days of total hospital stay (difference in means 8, 95% CI 2.67, 13.3, p = 0.001) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The median length of hospital stay of all the included patients was 17 days (IQR 9-34). The group receiving hypotonic solutions had a longer stay (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) than the group receiving isotonic solutions (14 days IQR 8-30) (p = 0.000). The use of hypotonic solutions was associated with 8 more days of total hospital stay (difference in means 8, 95% CI 2.67, 13.3, p = 0.001) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric studies, although smaller in size, have demonstrated a similar trend in the volume burden associated with maintenance fluids. 14 , 15 Maintenance fluids are primarily used to prevent dehydration and to provide a source of glucose to prevent starvation ketosis. However, our data demonstrate that maintenance fluids are frequently given to patients with fluid in excess of hydration requirements and this practice may represent iatrogenic harm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in children have also demonstrated that a large fluid burden may result from non-resuscitation fluids, especially maintenance fluids. 14 , 15 Recently, Al-Lawati et al 15 demonstrated that fluid exposure frequently exceeded hydration requirements on day 3 of pediatric intensive care unit (PICU) admission. However, the degree to which non-resuscitation fluid in excess of hydration requirements impacts clinical outcomes has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Compound Sodium Lactate (CSL), containing lower sodium and chloride content, has been available and in use for nearly a century [ 3 ]. More recently, Plasma-Lyte 148 (PL) has become available as an alternative balanced fluid (composition closer to plasma) with a higher sodium concentration as compared to CSL (Additional file 1 ) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%